Przeprowadzanie zmian w okresie konwergencji rynków - Bełz, Grzegorz (Implementing change during market convergence, 2006)
Article discuses dilemmas of change implementation in the process of market convergence. It is based on case of emerging, new model of triple play services commercialization, which can be treated as example of three market sector convergence. The change process in such case shows both revolutionary as well as evolutionary characteristics. Author points out some basic rules of such a coexistence.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 185-192